STIMULASI KECERDASAN SPIRITUAL ANAK PADA PERIODE PENDIDIKAN PRANATAL DALAM PERSPEKTIF ISLAM - Laila, Qumi (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2009)
People in the world are provided with intelligence by the Lord, the intelligence is exactly what can make the difference between humans and other creatures. There are many kinds of intelligence that was found by experts, including three intelligence (Q), namely IQ, EQ, SQ. In general, people are more likely to pay attention to intelligence (IQ), when there is more intelligence main EQ. Along with developmental era, EQ also felt less able to provide meaning in human life, and finally found the type of supreme intelligence that is SQ or Spiritual Intelligence. Spiritual Intelligence spiritual been bestowed by God when humans are not born, but the need for stimuli that serves to maintain and develop that intelligence. The stimulation done by parents, especially the mother as the person most close and interact most with the fetus. This research discussed spiritual intelligence in Islam and how to stimulate spiritual intelligence in the perspective of Islam. It is a library research; the authors use content analysis to analyze the content of the various literature which may include books, journals, articles from the internet, and thesis. And finally this research lead to the conclusion that parents can stimulate spiritual intelligence in children who are still in the prenatal period, to perform or to practice diligently, diligently worship, reading the Qur'an, dhikr, play religious songs or sholawat to the child in the womb, noble, telling tales of the Prophet to the child in the womb.